Effects of Sugammadex versus Neostigmine on Intraoperative Coagulation Profiles in Patients with Thyroidectomy - Zhao D; Fang J; Xiong W; Lin J; Chen W; Wu C (Dove Medical Press, 2021)
Dizhou Zhao, Jieyu Fang, Wei Xiong, Jun Lin, Wanmei Chen, Chujun Wu Department of Anesthesia, The First Affiliated Hospital of Sun Yat-Sen University, Guangzhou, People’s Republic of ChinaCorrespondence: Jieyu FangDepartment of Anesthesia, The First Affiliated Hospital of Sun Yat-Sen University, No. 56 Zhongshan Road II, Guangzhou, People’s Republic of ChinaTel + 86-13660121136Email fangjy@mail.sysu.edu.cnBackground: Sugammadex has been a revolutionary reversal of neuromuscular blockade. It is known to be highly efficient. However, a change in the coagulation profile is one of the most dangerous potential complications which is a concern for both surgeon and anesthetist. Bleeding may cause hypovolemic shock, hematoma, and so on. To investigate the effects of sugammadex on coagulation profiles in patients with thyroidectomy, we compared patients that were treated with either sugammadex or neostigmine.Patients and Methods: Eighty patients with thyroid neoplasms undergoing thyroidectomy were randomly allocated to sugammadex group (group S) or neostigmine group (group N). Induction of anesthesia was preformed using propofol, sufentanil, and rocuronium. Group S received sugammadex 2.0mg/kg after trachea intubation, similarly Group N received neostigmine 40 μg/kg, for reversal of rocuronium-induced neuromuscular blockade. The intraoperative coagulation profiles were monitored after the rocuronium injection (T0), 10 minutes after reversal (T1) and 30 minutes after reversal (T2) by testing activated partial thromboplastin time (APTT), prothrombin time (PT), fibrinogen (FIB), thrombin time (TT), and TEG-Haemonetics. Amount of bleeding was recorded during perioperative period.Results: There was no significant difference in the thromboelastogram, APTT, PT, FIB, or TT measurements at each time point in Group N. The reaction time (R time) and kinetics time (K time) of Group S in T1 were significantly longer than the corresponding times at T0 and T2, and the R times were significantly longer than those in Group N at the same time points (P< 0.05). Additionally, in Group S, the APTT was prolonged in T1 and returned to normal in T2.Conclusion: The result showed that sugammadex provided transient efficacy in prolonging the coagulation parameters, while neostigmine did not change the coagulation profile.Keywords: sugammadex, neostigmine, TEG-Haemonetics, coagulation, thyroidectomy